Inhibiting degradation of cellulose dissolved in ionic liquids via amino acids. Issue 10 (3rd May 2019) - Yang, Jiming; Lu, Xingmei; Yao, Xiaoqian; Li, Yao; Yang, Yongqing; Zhou, Qing; Zhang, Suojiang
Abstract : By addingl -arginine, cellulose degradation was inhibited in [C4 mim]Cl with a 90% regeneration rate after 24 h at 130 °C. Abstract : Although ionic liquids (ILs) are efficient solvents for dissolving cellulose, long time dissolution (for example ≥24 h) could lead to cellulose degradation, especially at high temperatures (for example ≥130 °C), limiting the use of ILs in the cellulose industry. On the premise of sufficient dissolution, inhibiting cellulose degradation in 1-butyl-3-methylimidazolium chloride [C4 mim]Cl, 1-ethyl-3-methylimidazolium chloride [C2 mim]Cl and 1-allyl-3-methylimidazolium chloride [Amim]Cl at 130 °C was achieved by the addition of amino acids. The results show that the cellulose regeneration rate increased from 0.00% to 90.02% at 130 °C for 24 h when 1.25 wt% ofl -arginine was added to [C4 mim]Cl. It is concluded thatl -arginine can form an intermolecular hydrogen bond with one of the three ipsilateral hydroxyls of cellulose, which prevents the cation [C4 mim] + or anion Cl − from simultaneously forming three hydrogen bonds with the three ipsilateral hydroxyls of cellulose, successfully inhibiting cellulose degradation. This work expands the application of ILs in the cellulose industry.